pls help me!! even just one answer is helpful!

1. Let [tex]f(x) = 4x - 7, g(x) = (x+1)^{2},[/tex] and, [tex]s(x) = f(x) + g(x).[/tex] What is s(3)?

2. Let [tex]f(x) = 2x^2 + 3x - 9, g(x) = 5x + 11,[/tex] and [tex]h(x) = -3x^2 + 1.[/tex] Find f(x) - g(x) + h(x).

3. The function f(x) satisfies [tex]f(\sqrt{x+1}) = \frac{1}{x}[/tex] for all x ≥ -1, x ≠ 0. Find f(2).

Respuesta :

Answer:

1) s(x) = f(x) + g(x) = 4x - 7 + x² + 2x + 1 = x² + 6x - 6

=> s(3) = 3² + 6.3 - 6 = 9 + 18 - 6 = 21

2) f(x) - g(x) + h(x)

= 2x² + 3x - 9 - (5x + 11) + ( - 3x² + 1)

= - x² - 2x - 19

3) we have:

sqrt(x + 1) = 2

=> x + 1 = 4

<=> x = 3

with x = 3 => f(2) = 1/3